A Novel Approach Certificate Revocation in MANET using Fuzzy logic - Jayanthi. E; Mohammed Ali Hussain (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
Due to the advent developments in the Information and Communication Technology (ICT) based environment, Mobile ad hoc networks (MANETs) have fascinated much concentration because of their mobility and easy deployment. At the same time, their wireless and vibrant features make them susceptible to wide range of types of security attacks when compared to the traditional wired networks. The prime challenge is to assure security in the network components and services. To work out the challenge, novel security measures are put forward for effective and secured communication. In our proposed work, we discuss the need for Security in MANET, focusing on certificate revocation. Providing security is challenging tasks due to its key features. Different authentication techniques, Digital certificate and components of Public Key Infrastructure are also discussed. The certificate revocation is a challenging task in MANETs due to absence of centralized repositories and trusted authorities. The different methods of certificate revocation using cluster based mechanism is analyzed and compared. The principle, advantages and disadvantages of certificate revocation are also compared. And the novel Certificate revocation techniques using fuzzy is discussed with reduced overhead.